The Tin Snail - McAllister, Cameron; Usher, Sam (New York : Delacorte Press, 2016)
"A thirteen-year-old French boy tries to save his father's job by inventing a special kind of car, but it isn't easy--especially when the Nazis are planning to steal his design"--
"Originally published...by Random House Children's Publishers UK, London, in 2014."
Based on the true story of the Citroen 2CV car.
Keywords: Automobiles -- Design and construction -- Fiction; Fathers and sons -- Fiction; Italians -- France -- Fiction; France -- History -- German occupation, 1940-1945 -- Fiction; World War, 1939-1945 -- Underground movements -- France -- Fiction; v; Automobiles -- Design and construction -- Fiction; Fathers and sons -- Fiction; Italians -- France -- Fiction; France -- History -- German occupation, 1940-1945 -- Fiction; World War, 1939-1945 -- Underground movements -- France -- Fiction